Incidence of reproductive disorders in buffaloes under field conditions of Andhra Pradesh - RAJU, K G S; NAIDU, K VENUGOPAL; RAO, K S (The Indian Journal of Animal Reproduction, 2007)
The data of 8,193 infertility camps conducted from 1997 -2002 were analyzed to study the incidence ofvarious reproductive· disorders in 4, 51, 344 buffaloes of Andhra Pradesh. The percentage of various reproductivedisorders recorded were inactive ovaries (:55.79), silent heat (9.44), repeat breeding (7.57), endometritis (19.40),cystic ovaries (1.48), persistent corpus luteum (0.59), underdeveloped genitalia (3 .23), hypoplasia of ovaries(0.001), salphingitis (0.20), pyometra (0.25), cervicitis (1.28), kinked cervix (0.01), vaginitis (0.71) and others(0.05) in buffaloes under field conditions.
Keywords: Reproductive disorders; Incidence; Buffaloes